Management Perkantoran - MAULIDIYAH, SOFI (Maliki Interdisciplinary Journal, 2025)
Office management has a very important role in supporting the smoothness and efficiency of the organization. Good management will make operational activities smoother and increase employee productivity. However, many organizations still face challenges in implementing optimal office management. Many companies have started to switch to digital systems, project management applications and cloud-based services. However, without the right strategy, implementing this technology can actually increase the workload and get resistance from employees. Through this discussion, it is hoped that readers can gain a deeper understanding of the importance of good office management and how its implementation can have a positive impact on the sustainability of a company or organization.